2015
DOI: 10.2174/1874350101508010054
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Sensation Seeking and Paranormal/Anomalous Experiences

Abstract: Sensation seeking is the tendency to pursue sensory pleasure and excitement. A body of research indicates that sensation seeking may contribute to paranormal/anomalous experiences. Examination of relations between sensations seeking and paranormal beliefs has resulted in a limited body of research. This paper hypothesizes that both – sensation seeking and paranormal/anomalous experiences – will be significantly and positively correlated. Two samples of 446 females and 162 males (Mage = 8.60, SD = 4.65) filled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…That indicated that both male and female subjects share similar levels of paranormal beliefs. Such results are aligned with some previous research findings (Vitulli, Tipton, & Rowe, 1999) and contradict others (Parra, 2015;Utinans et al, 2015). Since calculated p value in this study is considered marginal, it could go either way.…”
Section: Discussionsupporting
confidence: 91%
“…That indicated that both male and female subjects share similar levels of paranormal beliefs. Such results are aligned with some previous research findings (Vitulli, Tipton, & Rowe, 1999) and contradict others (Parra, 2015;Utinans et al, 2015). Since calculated p value in this study is considered marginal, it could go either way.…”
Section: Discussionsupporting
confidence: 91%
“…H4: SPEs should be more commonly reported by females than by males and paranormal beliefs should be stronger in females than in males – supported in 11 out of 13 studies (Blackmore, 1997; Castro et al., 2014; Emmons & Sobal, 1981; Fox, 1992; R. Lange & Houran, 1998, 1999; Parra, 2015a; Persinger & Richards, 1991; Randall & Desrosiers, 1980; Vitulli et al., 1999; Wolfradt, 1997). However, no consistent gender-related differences in SPE rates were found by Dagnall et al.…”
Section: Hypothesesmentioning
confidence: 94%
“…Contrasted to other types of tourism experiences, it is interesting to find that "fear" emotions, mostly known as negative emotions, are more likely to contribute to a positive paranormal experience. This could be explained by the nature of paranormal experience, which is to pursue something abnormal and experience something thrilling (Parra, 2015). As a type of special interest tourism, if their initial expectations are not met, the overall experience is more likely to be unsatisfied; for paranormal tourists, the essential desire is to be sacred and surprised (Pharino, 2019).…”
Section: Experiences In Paranormal Tourism 229mentioning
confidence: 99%